S-Sulfhydration of ATP synthase by hydrogen sulfide stimulates mitochondrial bioenergetics - Módis, Katalin; Ju, YoungJun; Ahmad, Akbar; Untereiner, Ashley A.; Altaany, Zaid; Wu, Lingyun; Szabo, Csaba; Wang, Rui (Pharmacological research, 2016)
[Display omitted] Mammalian cells can utilize hydrogen sulfide (H2S) to support mitochondrial respiration. The aim of our study was to explore the potential role of S-sulfhydration (a H2S-induced posttranslational modification, also known as S-persulfidation) of the mitochondrial inner membrane protein ATP synthase (F1F0 ATP synthase/Complex V) in the regulation of mitochondrial bioenergetics. Using a biotin switch assay, we have detected S-sulfhydration of the α subunit (ATP5A1) of ATP synthase in response to exposure to H2S in vitro. The H2S generator compound NaHS induced S-sulfhydration of ATP5A1 in HepG2 and HEK293 cell lysates in a concentration-dependent manner (50–300μM). The activity of immunocaptured mitochondrial ATP synthase enzyme isolated from HepG2 and HEK293 cells was stimulated by NaHS at low concentrations (10–100nM). Site-directed mutagenesis of ATP5A1 in HEK293 cells demonstrated that cysteine residues at positions 244 and 294 are subject to S-sulfhydration. The double mutant ATP synthase protein (C244S/C294S) showed a significantly reduced enzyme activity compared to control and the single-cysteine-mutated recombinant proteins (C244S or C294S). To determine whether endogenous H2S plays a role in the basal S-sulfhydration of ATP synthase in vivo, we compared liver tissues harvested from wild-type mice and mice deficient in cystathionine-gamma-lyase (CSE, one of the three principal mammalian H2S-producing enzymes). Significantly reduced S-sulfhydration of ATP5A1 was observed in liver homogenates of CSE−/− mice, compared to wild-type mice, suggesting a physiological role for CSE-derived endogenous H2S production in the S-sulfhydration of ATP synthase. Various forms of critical illness (including burn injury) upregulate H2S-producing enzymes and stimulate H2S biosynthesis. In liver tissues collected from mice subjected to burn injury, we detected an increased S-sulfhydration of ATP5A1 at the early time points post-burn. At later time points (when systemic H2S levels decrease) S-sulfhydration of ATP5A1 decreased as well. In conclusion, H2S induces S-sulfhydration of ATP5A1 at C244 and C294. This post-translational modification may be a physiological mechanism to maintain ATP synthase in a physiologically activated state, thereby supporting mitochondrial bioenergetics. The sulfhydration of ATP synthase may be a dynamic process, which may be regulated by endogenous H2S levels under various pathophysiological conditions.